Feedback regulation of Cyclooxygenase-2 transcription ex vivo and in vivo - Ishikawa, Tomo-o (2008)
Cyclooxygenase-2 (COX-2) is a rate-limiting enzyme for prostaglandin biosynthesis. Its inducible expression is regulated by complex pathways. To monitor Cox-2 transcriptional activity in vivo, we generated a knock-in mouse expressing a firefly luciferase reporter. In this study we examined, by comparing luciferase activity of Cox-2(luc/+) and Cox-2(luc/-) cells and mice, effects of prostanoid products on Cox-2 promoter transcriptional activation. In peritoneal macrophages, luciferase induction by LPS in Cox-2(luc/-) cells was less than that of Cox-2(luc/+) cells. However, in the presence of PGE(2), induction was comparable, suggesting positive Cox-2 feedback regulation by PGE(2) occurs for macrophages. In contrast, feedback modulation was not observed in TPA-induced Cox-2(luc/+) and Cox-2(luc/-) mouse embryonic fibroblasts (MEFs). Using non-invasive in vivo imaging, we observed negative feedback regulation of Cox-2 expression during paw inflammation in living mice. Our results suggest Cox-2 expression is regulated by cell type specific feedback mechanisms, both in cultured cells and in living animals.